ANALISIS STABILITAS TUBUH BENDUNGAN PADA BENDUNGAN UTAMA PROYEK WADUK BENDO PONOROGO - moch sholeh; M Suhartono; Nur Anisfi Choirini (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
The work of embankment in the main dam with an upright core consists of 5 pile zones: the core, filter, random, rock, and rip-rap. There was difference in planning and implementation of embankment filling. Random and rock used quarry Bondrang in planning but blasting upstream of the excavated material was used in implementation. This difference is because there are social problems with the community surrounding the Bondrang quarry. The purpose of this thesis is to repair the dam foundation, to find out the seepage discharge, to analyze the possibility of piping, to determine the safety factor of slope stability in the dam, and to determine RAB Maindam of Bendo Dam Project Ponorogo. The required data were of the geologic of the dam foundation, embankment materials, cross-sectional images of the dam body, and dam technical. Repairing the foundation using 3 methods : curtain grouting, consolidated grouting and blanket grouting; and for seepage calculations using the Cassagrande formula; to calculate safety figures using the Fellenius method and use the Geo-Studio 2012 application, the Seep / W program to find out the seepage discharge and the Geo-slope program to find out slope stability in maindam. The analysis resulted in 3 methods of repairing dam: curtain grouting with a depth of 39.83m, consolidated grouting with a depth of 5m, and blanket grouting with a depth of 15m; seepage discharge capacity <1% passing water average meaning safe; velocity seepage (7,3816 x 10-7m/sec) < velocity critical (0,004017m/sec) and 11,97 > 4 meaning safe for piping; >1.5 slope stability in various conditions without earthquake load meaning safe; 1.2 slope stability in various conditions with earthquake load meaning safe; the estimated cost IDR290,388,884,070.62 for main dam